2014
DOI: 10.1111/jnc.12756
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5/p35 is required for motor coordination and cerebellar plasticity

Abstract: Previous studies have implicated the role of Purkinje cells in motor learning and the underlying mechanisms have also been identified in great detail during the last decades. Here we report that cyclin-dependent kinase 5 (Cdk5)/p35 in Purkinje cell also contributes to synaptic plasticity. We previously showed that p35(-/-) (p35 KO) mice exhibited a subtle abnormality in brain structure and impaired spatial learning and memory. Further behavioral analysis showed that p35 KO mice had a motor coordination defect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 76 publications
0
22
0
1
Order By: Relevance
“…Moreover, a long-term potentiation (LTP) induction protocol evoked significantly reduced potentiation in L7-p35 cKO PCs. These results indicate that p35 is involved in both LTD and LTP at the PF-PC synapse (He et al 2014). In summary, He et al (2014) demonstrated that Cdk5/p35 activity in PCs is required for proper motor coordination and for the formation of two forms of long-term synaptic plasticity of the cerebellum, LTD and LTP.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…Moreover, a long-term potentiation (LTP) induction protocol evoked significantly reduced potentiation in L7-p35 cKO PCs. These results indicate that p35 is involved in both LTD and LTP at the PF-PC synapse (He et al 2014). In summary, He et al (2014) demonstrated that Cdk5/p35 activity in PCs is required for proper motor coordination and for the formation of two forms of long-term synaptic plasticity of the cerebellum, LTD and LTP.…”
mentioning
confidence: 94%
“…In this issue, He et al (2014), provide new insights into the role of Cdk5/p35 in motor coordination and cerebellar plasticity. The authors' initial investigations of previously developed p35 deficient (p35 À/À ) transgenic mice identified impaired ability to maintain balance without noticeable muscle weakness (He et al 2014).…”
mentioning
confidence: 99%
See 3 more Smart Citations